Unravelling perceptions of Eurasian beaver reintroduction in Great Britain. Issue 2 (8th August 2019) - Auster, Roger Edward; Puttock, Alan; Brazier, Richard
Abstract : International Union for the Conservation of Nature (IUCN) guidelines state that anticipated impacts must be considered in wildlife reintroduction, including the impacts on humans. Further, since reintroduction projects can be halted by resulting human–wildlife conflicts or human–human conflicts about wildlife, the perceptions of stakeholders and publics are of great importance. Eurasian beaver ( Castor fiber ) reintroduction is being debated in Great Britain at a devolved level. A decision has already been taken in Scotland to allow beavers already present to remain, while a number of reintroduction trials are taking place in England (both fenced and unfenced). There are also proposals for a reintroduction trial in Wales. We use a sub‐set of results from a nationwide survey ( n = 2, 759) to identify four social areas that we propose decision‐makers should consider in the debate: key stakeholder perceptions; engagement methods; attitudes towards legal protection and management responsibilities; and support for management techniques. In this paper, we investigate the complex social dimensions of wildlife reintroduction and we argue that emphasis should be placed on the need to recognise societal perceptions of potential management solutions, beyond perceptions of reintroduction itself. This is paramount in order to develop a management strategy that is more likely to garner social support and reduce potential future conflicts, should beaver reintroduction proceed. Abstract : Wildlife reintroduction projects can be halted by potential human–wildlife conflicts or human–human conflicts about wildlife. Eurasian beaver ( Castor fiber ) reintroduction is being debated in Great Britain with decision‐making devolved to the Scottish, English, and Welsh governments. We use a subset of results from a nationwide survey ( n = 2, 759) to identify four social areas that we propose decision‐makers should consider and we argue that emphasis should be placed on the need to recognise societal perceptions of potential management solutions, beyond perceptions of reintroduction itself, to develop a management strategy more likely to reduce potential future conflicts.